Pengembangan Pengembangan Instrumen Penilaian Penerapan Deep Learning dalam Pembelajaran Kimia: Analisis Model Rasch - Yerimadesi; Iryani; Faizah Qurrata Aini; Fauzana Gazali; Nofri Yuhelman; Rivo Juita Sudirman; Diva Salsabila; Zaqiya Zahwa Alifa; Mentari Az Zahra (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop a valid and reliable assessment instrument for the application of deep learning in high school chemistry instruction. The development of the instrument is based on Wilson’s Four Building Blocks approach (2005), which includes construct maps, items, item scores, and measures. The study was conducted with 271 twelfth-grade students from three public high schools in West Sumatra, selected through purposive sampling. Data were collected using a student perception questionnaire designed based on the four pillars of deep learning implementation: graduate profile dimensions, learning principles, learning experiences, and learning frameworks. Content validity was analyzed using Aiken’s V, while empirical validity and reliability were tested using the Rasch Model. The results showed an average Aiken’s V value of 0.90, indicating excellent content validity. Rasch analysis yielded a respondent reliability of 0.97 and an item reliability of 0.95, with fit statistics within the ideal range and supporting construct unidimensionality. From the initial 116 items, the final instrument consists of 46 items that passed through a rigorous empirical selection process to ensure high measurement quality. Thus, this instrument is suitable for evaluating the level of deep learning implementation at the elementary to intermediate levels in high school chemistry education.